Development of Social Responsibility in order to Implement Knowledge Awareness Through Character Education Internalization - Adnyani, Ni Ketut Sari; Mandriani, Ni Nyoman; Asrini, Ni Kadek Putus (Universitas Pendidikan Ganesha, 2018)
The purpose of this research are: (1) to know the importance of Character Education given to the students; (2) to know the relevance of Character Education in developing social responsibility attitude for learners; and (3) to know the internalization of Character Education in enriching the knowledge of learners in order to cultivate a positive attitude to fill the independence. Research method, This research use Educational Research and Development model. The process of development and validation of educational products in this research is in the form of development of learning model of nationalism based on local genius. Research on Define and design stage is done on research setting: educator, school, student and library. Development phase, which is limited trial in accordance with the design will be done in SD Negeri 2 Datah and Elementary School 6 Tianyar by using setting classes in learning PKn. The classes of PKn subjects involved in the develompment stage are chosen purposively (purposively) according to the research focus. Determination of research samples in trials conducted by random sampling. Outcome: Character Education is given to learners, its relevance influence to student's social responsibility attitude.